Zein/Polysaccharide Nanoscale Electrostatic Complexes: Preparation, Drug Encapsulation and Antibacterial Properties - Lotos, Elena-Daniela; Mihai, Marcela; Vasiliu, Ana-Lavinia; Rosca, Irina; Mija, Alice; Simionescu, Bogdan C.; Pispas, Stergios (Nanomaterials (Basel, Switzerland), 2024)
Characterization of zein aqueous solutions, as a function of the ethanol content and pH, was performed, giving information on the zein aggregation state for the construction of complexes. The aggregation state and surface charge of zein was found to depend on the mixed solvent composition and pH. Nonstoichiometric complex nanoparticles (NPECs) were prepared by electrostatically self-assembling zein, as the polycation, and sodium alginate or chondroitin sulfate, as the polyanions, at a pH of 4. A wide range of parameters were investigated: the alcohol–water content in the zein solutions, the charge molar ratios, the solution addition order and the addition rate. The resulting nanoparticles were characterized by dynamic and electrophoretic light scattering, circular dichroism and scanning electron microscopy. The smallest size for the NPECs (100 nm) was obtained when the polysaccharides acted as the titrate with an addition rate of 0.03 mL·min−1. The NPECs with the best characteristics were selected for loading with ciprofloxacin and then deposited on a cellulosic material in order to evaluate their antibacterial activity. Substantial drug encapsulation with desired drug release profiles were found together with notable antibacterial efficiency, showing the tunability of the properties for both the zein and its complexes with polysaccharides, together with their application potential in the biomedical field.